Interpretation of the Verses of Education in Surah Luqman - Mahrus As'ad (At-Tarbiyat, 2021)
This study aims to determine the interpretation of educational verses in Surah Luqman, which includes several aspects of education, including educational material, educational methodology, educators, and students. This study uses a qualitative approach, namely describing or outlining the interpretation of educational verses in Surah Luqman verses 13-19. The way to describe the data is done through several expert opinions from various sources. The data collection technique was carried out by using library research techniques. The findings of this study are that Luqman provides education to his children by using love, example, advice, and good greetings. And the contents contained in the letter al-Luqman verses 12-19 are monotheism, birrul waalidain, muhasabatun nafsi, establishing prayer, admonishing ma'ruf nahi munkar, patient, not arrogant, superficial in speech, attitude and deed.